Study protocol: an effectiveness, cost-effectiveness, and process evaluation of headspace Denmark - Siv T. B. Bjørkedal; Siv T. B. Bjørkedal; Thomas N. Christensen; Thomas N. Christensen; Rie M. Poulsen; Rie M. Poulsen; Anne Ranning; Anne Ranning; Anne A. E. Thorup; Anne A. E. Thorup; Merete Nordentoft; Merete Nordentoft; et al. (Frontiers in Public Health)
IntroductionSince 2013, headspace Denmark has been offered in specific areas to adolescents and young adults between 12 and 25 years, to promote youth mental health and wellbeing. Headspace provides free counselling and support, primarily delivered by trained volunteers in the headspace centres and provides information and knowledge about youth mental health, and headspace services, through community engagement. Until now, effectiveness evaluation of the Danish headspace centres has not been conducted.MethodsPresent study consists of (1) an effectiveness evaluation designed as a propensity score matched quasi-experimental trial, where the exposed person (n = 1,500), in this case the young person receiving counselling sessions at headspace, will be matched by using propensity scores to six unexposed individuals. (2) A cost-effectiveness evaluation (3) a process evaluation with predominantly qualitative methods to investigate the implementation of key activities of headspace, their mechanisms of change, and interactions with contextual factors.Discussionheadspace centres have achieved national endorsement and are implemented in 30 municipalities in Denmark. Thus, there is a need to investigate the effectiveness of the services. Results from the evaluation can also contribute to new knowledge targeted at international youth mental health promotion initiatives. However, this evaluation is limited by selection bias since it is not possible to separate the impact of the intervention from the impact of help-seeking behaviour.